The dynamics of DNA methylation fidelity during mouse embryonic stem cell self-renewal and differentiation - Zhao, Lei; Sun, Ming-an; Li, Zejuan; Bai, Xue; Yu, Miao; Wang, Min; Liang, Liji; Shao, Xiaojian; Arnovitz, Stephen; Wang, Qianfei; He, Chuan; Lu, Xuemei; et al. (Genome Research, 2014)
The faithful transmission of DNA methylation patterns through cell divisions is essential for the daughter cells to retain a proper cell identity. To achieve a comprehensive assessment of methylation fidelity, we implemented a genome-scale hairpin bisulfite sequencing approach to generate methylation data for DNA double strands simultaneously. We show here that methylation fidelity increases globally during differentiation of mouse embryonic stem cells (mESCs), and is particularly high in the promoter regions of actively expressed genes and positively correlated with active histone modification marks and binding of transcription factors. The majority of intermediately (40%–60%) methylated CpG dinucleotides are hemi-methylated and have low methylation fidelity, particularly in the differentiating mESCs. While 5-hmC and 5-mC tend to coexist, there is no significant correlation between 5-hmC levels and methylation fidelity. Our findings may shed new light on our understanding of the origins of methylation variations and the mechanisms underlying DNA methylation transmission.
10.1101/gr.163147.113